Illuminating the Goal: rDzogs chen and Doxography in 14th-century Tibet - Albion M. Butters (Suomen Itämainen Seura, 2022)
This study explores the philosophical, canonical and doxographical contributions of one of Tibet’s greatest thinkers, Klong chen rab ’byams pa (1308–1363), or Longchenpa, particularly as presented in his detailed overview of Buddhist tenet-systems, the Grub mtha’ mdzod (The Precious Treasury of Spiritual Systems). While the bulk of the previous scholarship on this scholar has focused almost exclusively on his writings on the tantric modality of Atiyoga (or rDzogs chen), this study addresses Klong chen pa’s endeavors to integrate that school of thought with the other Buddhist vehicles (Sūtrayāna and Mantrayāna) by means of parallel techniques and a polysemic hermeneutic. Furthermore, it questions a number of critiques brought against rDzogs chen. Furthermore, by locating Klong chen pa biographically and textually in relation to the other seminal figures of 14th-century central Tibet (e.g., Bu ston, O rgyan gling pa, Dol po pa), this study shows the precise nature of his wide-ranging contributions to canonical construction within the rNying ma tradition of Tibet and the particularities involved with his interpretation of Buddhism’s two-reality theory (relative and ultimate) in relation to the Svātantrika and Prāsaṅgika schools of Madhyamaka philosophy. In the process, it provides context for understanding Klong chen pa as a complex figure, with both scholarly and practical soteriological concerns, and his engagement with the most critical debates of his time.